Kesulitan Guru IPA SMP Kelas VIII Dalam Merencanakan dan Melaksanakan Asesmen - Ridha Pangastuti; Rini Rita T. Marpaung; Berti Yolida (Universitas Lampung, 2017)
This study was to identify the difficulties of 8th grade science teachers in Gedong Tataan, Pesawaran in the academic year of 2016/2017 in planning and implementing assessment for their students.Thus, all of 8th grade science teachers were selected by saturated sampling technique. This research design was descriptive. The data were from the questionnaire and interviews that were analyzed descriptively. The results showed that the average of difficulty experienced by teachers in planning and implementing the assessment was sufficient. The highest percentage that causes the teacher to have difficulty in assessment planning was determine learning goals according to Basic Competence. While the highest percentage that causes the teacher to have difficulty in implementing the assessment was the implementation of the affective domain assessment,especially in observing the affective aspect and conditioned the implementation of the assessment.Penelitian ini bertujuan untuk mengidentifikasi kesulitan guru IPA kelas VIII SMP Negeri se-Kecamatan Gedong Tataan Kabupaten Pesawaran Tahun ajaran 2016/2017 dalam merencanakan dan melaksanakan asesmen. Sampel penelitian adalah seluruh guru IPA kelas VIII yang dipilih dengan teknik sampling jenuh. Desain penelitian adalah desain deskriptif. Data diperoleh dari hasil angket dan wawancara pada guru yang dianalisis secara deskriptif. Hasil penelitian menunjukkan rata-rata kesulitan yang dialami guru dalam merencanakan dan melaksanakan asesmen tergolong cukup, persentase tertinggi yang menyebabkan guru cukup kesulitan dalam merencanakan asesmen adalah menetapkan tujuan pembelajaran yang sesuai dengan KD. Sementara persentase tertinggi yang menyebabkan guru cukup kesulitan dalam melaksanakan asesmen adalah dalam pelaksanaan asesmen ranah afektif, terutama dalam mengamati aspek sikap dan mengkondisikan pelaksanaan asesmen.Kata kunci: asesmen, guru IPA, kesulitan, melaksanakan, merencanakan